P1485SEVELAMER USE IS ASSOCIATED WITH DECREASED VITAMIN K LEVELS IN HEMODIALYSIS PATIENTS: RESULTS FROM VITAMIN K ITALIAN (VIKI) STUDY. (6th June 2020) - Fusaro, Maria; Aghi, Andrea; Khairallah, Pascale; Gallieni, Maurizio; Cozzolino, Mario Gennaro; Russo, Domenico; Mereu, Maria Cristina; Ravera, Maura; Tripepi, Giovanni Luigi; Nickolas, Thomas
Abstract: Background and Aims: Sevelamer (S) is a phosphate binding drug used to treat hyperphosphatemia in patients with CKD. Our aim was to evaluate the hypothesis that the use of (S) could interfere with Vitamin K absorption in hemodialysis (HD) patients of VIKI study. Method: We tested this hypothesis in VIKI, a cross-sectional study of 387 hemodialysis patients, we established the prevalence of vitamin K deficiency and to assessed the relationship between vitamin K status, vertebral fractures, vascular calcification. We determined serum concentrations of vitamin 25(OH)D; alkaline phosphatase (ALP); vitamers K1, MK4, MK5, MK6, MK7; osteocalcin (BGP) and Matrix Gla Protein (MGP). We highlighted that MK4 deficiency was the strongest predictor of aortic calcification (OR, 2.82; 95% CI, 1.14–7.01) while vitamin K1 deficiency was the strongest predictor of vertebral fractures fractures (OR: 2.94; 95% CI, 1.38–6.26). Results: 163 of 387 patients (42.1%) were treated with Sevelamer. There were no differences in levels of 25(OH)D, K1, MK5, MK6 and MK7 among patients treated with and without Sevelamer. Remarkably, the prevalence of MK4 deficiency was higher in Sevelamer treated patients (13.5% vs 5.4%, p=0.005). Sevelamer treated patients also had higher median levels of ALK (89 UI/L vs 77.5 UI/L, p=0.001) and total BGP (210 mcg/L vs 152 mcg/L, p=0.002) and lower median levels of total MGP (16.4 nmol/L vs 20.3 nmol/L, p=0.037) (Table 1 and Figure 1 ). In multivariable logistic regression, the odds ratio of MK4 deficiency (dependent variable) in patients treated with compared to without Sevelamer was ∼3-fold higher (OR: 2.64, 95% CI: 1.25-5.58, p=0.011) after adjustment for confounders of Vitamin K levels, including older age, previous myocardial infarction, type of HD, ALP, PTH, MGP, BGP, cholesterol and albumin. Conclusion: These data support the hypothesis that Sevelamer could interfere with MK4 absorption in HD patients. Longitudinal interventional studies are needed to prove the causal nature of these associations.